Differences in the rate of nicotine metabolism among smokers with and without HIV. (1st May 2019) - Ashare, Rebecca L.; Thompson, Morgan; Leone, Frank; Metzger, David; Gross, Robert; Mounzer, Karam; Tyndale, Rachel F.; Lerman, Caryn; Mahoney, Martin C.; Cinciripini, Paul; George, Tony P.; Collman, Ronald G.; et al.
Abstract : Objective: HIV-infected smokers lose more life years to tobacco use than to HIV infection. The nicotine metabolite ratio (NMR), a biomarker of CYP2A6, represents individual variation in the rate at which nicotine is metabolized and is associated with response to smoking cessation treatments. We evaluated whether HIV-infected smokers metabolize nicotine faster than HIV-uninfected smokers, which may contribute to the disproportionate smoking burden and may have important treatment implications. Design: We analysed baseline data from two clinical trials (NCT01710137; NCT01314001) to compare the NMR in HIV-infected smokers ( N = 131) to HIV-uninfected smokers ( N = 199). Methods: Propensity scores were used to match the groups 2 : 1 on characteristics that influence NMR: sex, race, BMI and smoking rate. Nicotine metabolites were assessed via liquid chromatography-tandem mass spectrometry methods and the ratio of 3-hydroxycotinine:cotinine was used to compute the NMR. Results: HIV-infected smokers had significantly higher NMR (mean = 0.47, SEM = 0.02) and were more likely to be in the highest NMR quartile compared with HIV-uninfected smokers (mean = 0.34, SEM = 0.02; P s < 0.001). Conclusion: The higher NMR observed among HIV-infected smokers may partially explain higher smoking rates and lower response to transdermal nicotine therapy. Understanding the mechanisms by which HIV and/or ART contribute to faster nicotine metabolism may guide the use of the NMR to personalize tobacco cessation strategies in this underserved population. Abstract : Supplemental Digital Content is available in the text